2019
DOI: 10.3390/ijms20040918
|View full text |Cite
|
Sign up to set email alerts
|

Differences of the Structure of Immune Regulatory Cell Populations between Cellular Material from Sonographically Detected Focal Thyroid Lesions and Peripheral Blood in Humans

Abstract: Focal thyroid lesions are common ultrasound findings with the estimated prevalence up to 67% of the population. They form characteristically enveloped regions with individual encapsulated microenvironment that may involve the specific distribution of immune system compounds—especially antigen presenting cells (APC). We analyzed and compared the most potent APC—plasmacytoid and conventional dendritic cells (DCs) subpopulations and three monocyte subpopulations as well as other immune cells—in peripheral blood a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It may occur in genetically predisposed individuals who are exposed to certain exogenous factors, such as iodine, selenium, smoking, bacterial and viral infections, allergies, radiotherapy or emotional stress. Endogenous factors such as age, sex, pregnancy, hormones and birth weight are also important [1,2,3,4]. GD develops due to a loss of immunological tolerance and reactivity to thyroid autoantigens, mainly directed against the thyrotropin receptor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may occur in genetically predisposed individuals who are exposed to certain exogenous factors, such as iodine, selenium, smoking, bacterial and viral infections, allergies, radiotherapy or emotional stress. Endogenous factors such as age, sex, pregnancy, hormones and birth weight are also important [1,2,3,4]. GD develops due to a loss of immunological tolerance and reactivity to thyroid autoantigens, mainly directed against the thyrotropin receptor.…”
Section: Introductionmentioning
confidence: 99%
“…GD develops due to a loss of immunological tolerance and reactivity to thyroid autoantigens, mainly directed against the thyrotropin receptor. This leads to the infiltration of this gland by T lymphocytes and B lymphocytes that produce antibodies specific for this disease entity, with a clinical manifestation of hyperthyroidism in the form of GD [1,2,3,4]. Recent studies have confirmed the importance of toll-like receptors (TLRs) and proinflammatory cytokines in the etiopathogenesis of autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation